Male sexuality after external continent urinary diversion type Mitrofanoff - Bouassida, M; Smaoui, W; Fourati, M; Mseddi, M A; Chabchoub, K; Chaabouni, A; Rekik, S; Rebai, N; Masmoudi, J; Hadjslimen, M; Mhiri, M N (Progrès en urologie (Paris), 2016)
To evaluate the influence of continent external urinary diversion type Mitrofanoff on male sexuality. Between 1992 and 2011, 140 patients underwent continent urinary diversion type Mitrofanoff at an academic hospital. Among 76 men, 46 were interviewed about their sexuality after this operation. This study was performed using a set of validated questionnaires (IIEF, DAN PSS and Urolife), grouped by the model of the CTMH. Patients were divided according to their marital status: group 1: patients married before surgery (15 cases), group 2: patients married after surgery (7 cases) and group 3: singles (24 cases). In the first group, the functional dimension of sexuality was positive with an overall score of 81%, the sexual discomfort score was assessed at 26 % and the sexual satisfaction score was 77%. In the second group, sexual function was considered conserved in all cases with a satisfaction score estimated at 98%. These patients reported a feeling of well-being following the disappearance of urinary incontinence with integrity of their body images. In contrast, in the last group, relatively impaired sexual function was noted (65%) with a satisfaction score estimated at 59%. These disorders were multifactorial, mainly related to neurological causal pathology. To our knowledge, this is the first study about male sexuality in patients with a continent urinary diversion type Mitrofanoff. Marital status has a major role in the sexuality of these patients. A prospective study with pre- and postoperative evaluation will better clarify the factors affecting sexuality in these patients.